Requirements for Structural Wood According to the CSCR-2010 and its Input in Research - González Beltrán, Guillermo (2025)
This paper discusses the relationship between the Costa Rican Seismic Code 2010 (CSCR-10) specifications and the research generated as result of those specifications. The use of timber for construction in Costa Rica has been growing since 2000, including the development of industrialized products such as structural laminated timber (GLULAM) and plywood. Consequently, the CSCR began to work on a chapter for the CSCR-10, in which the specification for structural timber is developed. The objective of this paper is to highlight the impact that the design codes and standard specification have had in the development of applied research in the field of design and construction of timber structures. To establish this relationship, the sections of the CSCR-10 are explained and then, the most relevant investigations are described. Finally, it is concluded that the CSCR has a great impact in the development of research of structural timber in Costa Rica. The previous is reflected on the eight investigations that have been carried out in a period of eight years.